Design of Efficient and Effective Wastewater Treatment Plant for Rubanda Town Council. - Twinamasiko, Caleb (Kabale University, 2023)
The main goal of this project is to design effective and efficient wastewater treatment plant. For the purpose of long durability and long usage of wastewater treatment facility. The wastewater generation was computed by forecasting population in thirty years (30). To obtain results, both scientific principles and engineering standards and ethical codes as well as laboratory tests results were put under consideration.